Existence of Three Positive Solutions to Some p-Laplacian Boundary Value Problems - Moulay Rchid Sidi Ammi; Delfim F. M. Torres (Discrete Dynamics in Nature and Society)
We obtain, by using the Leggett-Williams fixed point theorem, sufficient conditions that ensure the existence of at least three positive solutions to some p-Laplacian boundary value problems on time scales.